A Structural Investigation of CdTe(001) Thin Films on GaAs/Si(001) Substrates by High-Resolution Electron Microscopy - Kim, Kwang-Chon; Baek, Seung Hyub; Kim, Hyun Jae; Song, Jin Dong; Kim, Jin-Sang (SPRINGER, 2012)
Epitaxial CdTe thin films were grown on GaAs/Si(001) substrates by metalorganic chemical vapor deposition using thin GaAs as a buffer layer. The interfaces were investigated using high-resolution transmission electron microscopy and geometric phase analysis strain mapping. It was observed that dislocation cores exist at the CdTe/GaAs interface with periodic distribution. The spacing of the misfit dislocation was measured to be about 2 nm, corresponding to the calculated spacing of a misfit dislocation (2.6 nm) in CdTe/Si with Burgers vector of a[110]/2. From these results, it is suggested that the GaAs buffer layer effectively absorbs the strain originating from the large lattice mismatch between the CdTe thin film and Si substrate with the formation of periodic structural defects.
Keywords: MOLECULAR-BEAM EPITAXY; GROWTH; CDTE; SI(111)